Aluminum alloy foil for battery current collector and method for producing same
By controlling the Fe and Si content and the distribution of intermetallic compounds in the aluminum alloy foil, and using the TRC casting method, the problem of mechanical characteristics of aluminum foil for the positive electrode current collector of lithium-ion secondary battery decreased after low temperature heat treatment was solved, and high strength and high elongation aluminum alloy foil was achieved, meeting the needs of thin foil and high capacity.
Patent Information
- Application Number
- CN202380065577.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-22
- Filing Date
- 2023-09-20
- Publication Date
- 2025-04-25
AI Technical Summary
After low-temperature heat treatment of aluminum foil for the positive electrode current collector of the existing lithium-ion secondary battery, the tensile strength and elongation have significantly decreased, making it difficult to meet the needs of thin foil and high capacity.
By controlling the Fe and Si content in the aluminum alloy foil, and controlling the size and number density of intermetallic compounds on the surface, combined with a high cooling speed double-roll casting method (TRC casting method), high-strength and high elongation aluminum alloy foil after rolling and heat treatment at 120°C were prepared.
High tensile strength and elongation after foil rolling are achieved, and excellent mechanical characteristics are maintained after low temperature heat treatment at 120°C, which avoids breakage and increases the battery capacity per unit volume of the battery.
Smart Images

Figure BDA0005308118230000101
Abstract
Description
Technical Field
[0001] The present invention relates to an aluminum alloy foil for battery current collector and a method for producing the same. Background Art
[0002] Aluminum foil is typically used as the positive electrode current collector in lithium-ion secondary batteries. In recent years, achieving higher capacity within the limited volume of lithium-ion secondary batteries has required increasing the volume and density of the active material layer while also saving space for the current collector and other components. For example, the thickness of the aluminum foil used in the positive electrode current collector is approximately 12 μm, but further thinning is likely to be required in the future.
[0003] The manufacturing method of this lithium-ion secondary battery generally involves the following steps. First, a slurry made by mixing an active material, a binder resin, and a solvent is applied to the surface of a metal foil, such as aluminum foil, which will serve as a current collector. In this case, the slurry containing the positive electrode active material is applied to the metal foil that will serve as the positive electrode, and the slurry containing the negative electrode active material is applied to the metal foil that will serve as the negative electrode. Next, the metal foil coated with the slurry is heated, for example, at approximately 100 to 150°C to evaporate the solvent and dry it. Furthermore, to increase the density of the active material layer, the dried metal foil is pressed to obtain an electrode material. This pressing process is sometimes heated to improve pressing efficiency. The material is then further dried, for example, at approximately 120 to 160°C. The electrode material thus produced is cut or punched into the desired shape. The positive electrode material, separator, and negative electrode material are then stacked or wound, connected to a lead material, etc., and then housed in a casing or laminate bag. Next, an electrolyte solution is injected into the case or laminate bag, and after sealing, initial charge and discharge, aging, etc. are performed to produce a lithium ion secondary battery.
[0004] The manufacturing process described above is just one example. Aluminum foil, the current collector, undergoes a variety of processing and thermal processes, including pressing and winding. Thinner aluminum foil is more susceptible to breakage during these manufacturing steps. To ensure stable production without breakage, numerous technologies have been proposed to improve the mechanical properties of aluminum foil, particularly its tensile strength and elongation.
[0005] For example, Patent Document 1 discloses a technique in which the Fe content of an aluminum foil used as a current collector is set to 0.3% to 3.0% by mass, the Si content is set to 0.8% to 1.5% by mass, and the average diameter of large-particle crystallization products present in the aluminum alloy foil is controlled, thereby achieving mechanical properties such that the tensile strength is 170 N / mm when the foil thickness is 15 μm or less. 2 ~280N / mm 2 , the elongation is 4% to 10%.
[0006] In addition, Patent Document 2 discloses an aluminum alloy foil for battery collectors, which has an Fe content of 0.15% to 0.7% by mass, a Si content of 0.2% to 0.8% by mass, a Si content / Fe content ratio of 0.7 to 2.5, a tensile strength after rolling of 180 MPa or more, an elongation of 3.0% or more when the foil thickness is 12 μm, and the elongation characteristics are maintained even after low-temperature heat treatment.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: WO2010 / 100924 Pamphlet
[0010] Patent Document 2: Japanese Patent Application Laid-Open No. 2017-186629 Summary of the Invention
[0011] However, in the above-mentioned Patent Document 1, there is no record of the tensile strength and elongation after low-temperature heat treatment at 100 to 160°C as in the battery manufacturing process. In addition, as a method for manufacturing aluminum foil for current collectors, although the cooling rate of the melt in the process of obtaining the ingot is specified to be 100°C / sec to 500°C / sec, the maximum cooling rate in the embodiment remains at 182°C / sec, and although the casting method is continuous casting, there is no specific record. In addition, it is known that pure Al-based and Al-Fe-based aluminum foils are often used for positive electrode current collectors, but when these aluminum foils are subjected to low-temperature heat treatment at 100 to 160°C in the battery manufacturing process, the elongation decreases significantly. The reason for this phenomenon is still unclear, but it is predicted that since the heat treatment temperature is low, recovery and recrystallization are not easy to occur, resulting in a decrease in elongation.
[0012] In addition, in the aforementioned Patent Document 2, the highest value of tensile strength in the examples is 224 MPa. However, in order to meet the recent demand for thinner foils, further improvement in strength is required.
[0013] Therefore, the present invention is made in view of the above-mentioned problems, and its purpose is to provide an aluminum alloy foil for battery collectors that has excellent tensile strength and elongation after foil rolling and excellent tensile strength and elongation after low-temperature heat treatment expected in the battery manufacturing process, especially 120°C heat treatment.
[0014] In order to solve the above problems, the inventors conducted various studies and found that by controlling the Fe and Si contents in the aluminum alloy foil, as well as the size and number density of the intermetallic compounds present on the surface of the aluminum alloy foil, high strength and high elongation can be obtained after the foil is rolled and heat treated at 120°C.
[0015] That is, the present invention has the following features.
[0016] [1] An aluminum alloy foil for a battery current collector, characterized in that: (1) the composition of the aluminum alloy foil is as follows: an iron (Fe) content of not less than 0.15 mass % and less than 0.3 mass %, a silicon (Si) content of not less than 0.8 mass % and less than 1.5 mass %, and the remainder is composed of aluminum (Al) and unavoidable impurities; (2) the average equivalent circle diameter of intermetallic compounds present on the surface of the aluminum alloy foil is not more than 1.0 μm; (3) the number density of intermetallic compounds present on the surface of the aluminum alloy foil with an equivalent circle diameter greater than 3.0 μm is 2.0×10 2 Pieces / mm 2 the following.
[0017] [2] The aluminum alloy foil for a battery current collector according to [1], wherein the reduction in resistivity after heat treatment at 120°C for 1 hour relative to the resistivity after rolling is 0.03 μΩ·cm or more.
[0018] [3] The aluminum alloy foil for battery current collectors according to [1] or [2], wherein the tensile strength after rolling to a thickness of 12 μm is 235 N / mm 2 Above, the elongation is 3.0% or more.
[0019] [4] The aluminum alloy foil for battery current collectors according to any one of [1] to [3], wherein the aluminum alloy foil has a tensile strength of 225 N / mm after heat treatment at 120°C for 1 hour at a thickness of 12 μm. 2 Above, the elongation is 2.5% or more.
[0020] [5] A method for manufacturing an aluminum alloy foil for a battery collector, comprising: a casting step, wherein a molten metal having an iron (Fe) content of not less than 0.15 mass % and less than 0.3 mass %, a silicon (Si) content of not less than 0.8 mass % and less than 1.5 mass %, with the remainder consisting of aluminum (Al) and unavoidable impurities, is cast at a cooling rate of not less than 250°C / sec to obtain a cast plate; and a rolling step, wherein the cast plate is cold-rolled to obtain an aluminum alloy foil.
[0021] Even though the aluminum alloy foil for battery current collectors according to the present invention is made thinner, it has excellent tensile strength and elongation after rolling and low-temperature heat treatment at 120°C. Therefore, when used as a battery current collector, it is not easy to break during the battery process and can increase the battery capacity per unit volume. DETAILED DESCRIPTION
[0022] Hereinafter, embodiments of the present invention will be described in detail.
[0023] The aluminum alloy foil for battery current collectors according to the present invention contains predetermined amounts of Fe and Si, with the remainder consisting of Al and unavoidable impurities.
[0024] As described below, this aluminum alloy foil for battery current collectors has a composition containing Fe and a greater amount of Si than Fe. Due to this composition, Si exists not only as an Al-Fe-Si intermetallic compound bonded to Al and Fe, but also as elemental Si, unbonded with Al and Fe. This elemental Si is believed to exist as a solid solution in the aluminum matrix, or as a crystallized product composed solely of Si. The behavior of this elemental Si is believed to significantly influence the elongation properties of the aluminum alloy foil after low-temperature heat treatment.
[0025] In the manufacturing method of the present invention, by adopting the twin roll casting method (Twin Roll Casting casting method: TRC casting method) with a high cooling rate of the melt, elemental Si can not only be crystallized, but also can be supersaturatedly dissolved in the aluminum matrix. Even if the Si solid-dissolved in the aluminum matrix is easily diffused during low-temperature heat treatment, the supersaturatedly dissolved Si is separated out in the form of a precipitate consisting only of Si. Generally, it is speculated that the strain introduced by rolling in the manufacturing process of the aluminum foil cannot be fully removed during low-temperature heat treatment and becomes an uneven recovery state, causing the elongation to decrease. However, in the present invention, it is believed that the recovery state of the strain is changed by simultaneously recovering and precipitating Si when implementing low-temperature heat treatment. Therefore, even after low-temperature heat treatment, sufficient tensile elongation is also present.
[0026] Furthermore, it was found that the use of TRC casting resulted in excellent tensile strength and elongation after rolling, even with a low Fe content. This is believed to be because the rapid melt cooling rate of TRC casting refines the crystallized products in the aluminum alloy foil and increases the amount of Fe dissolved in the aluminum matrix.
[0027] Furthermore, when the Si content in the aluminum alloy foil is increased, crystallized products tend to coarsen, which may increase the occurrence of pinholes during the foil rolling process. However, this can be solved by refining the crystallized products through TRC casting.
[0028] [Iron content]
[0029] Iron (Fe) contained in the aluminum alloy foil for battery current collectors of the present invention is an element that improves tensile strength, elongation, and rollability by, for example, grain refinement, and is a component commonly added to aluminum foil. These effects are more significantly achieved by TRC casting.
[0030] The iron (Fe) content of the aluminum alloy foil for battery current collectors is 0.15% by mass or more and less than 0.3% by mass, more preferably 0.2% by mass or more and less than 0.27% by mass. Within the above range, the aluminum alloy foil for battery current collectors exhibits excellent mechanical properties. If the iron (Fe) content is less than 0.15% by mass, there is a tendency for the tensile strength to become insufficient. On the other hand, if the iron (Fe) content exceeds 0.3% by mass, there is a tendency to adversely affect the elongation after low-temperature heat treatment.
[0031] [Silicon content]
[0032] The silicon (Si) contained in the aluminum alloy foil for battery current collector of the present invention is increased in solid solubility in the aluminum matrix by TRC casting, and by making the crystallization products composed only of silicon (Si) finer, it is expected that the strength will be increased and the elongation after low-temperature heat treatment will be improved.
[0033] The silicon (Si) content of the aluminum alloy foil for battery current collectors is greater than 0.8% by mass and less than 1.5% by mass, more preferably greater than or equal to 0.85% by mass and less than 1.2% by mass. If the content is less than 0.8% by mass, it is difficult to obtain the desired elongation after low-temperature heat treatment. If the content is greater than 1.5% by mass, coarse crystallization and centerline segregation may occur during TRC casting, leading to increased pinhole formation and decreased elongation during foil rolling.
[0034] [Unavoidable impurities]
[0035] The remainder of the composition of the aluminum alloy foil for battery current collectors according to the present invention is composed of aluminum (Al) and inevitable impurities. These inevitable impurities are elements that inevitably enter the aluminum alloy foil during its production. These inevitable impurities may be present within a range that does not affect the properties of the aluminum alloy foil according to the present invention.
[0036] Examples of such unavoidable impurities include transition elements such as manganese (Mn), copper (Cu), vanadium (V), titanium (Ti), zirconium (Zr), chromium (Cr), and nickel (Ni), and elements such as magnesium (Mg), zinc (Zn), boron (B), gallium (Ga), and bismuth (Bi). The content of each of these elements in the aluminum alloy foil is preferably 0.05% by mass or less.
[0037] [Intermetallic compounds]
[0038] The average equivalent circle diameter of the intermetallic compounds present on the surface of the aluminum alloy foil for battery current collectors according to the present invention is 1.0 μm or less, preferably 0.8 μm or less. If it is within the above range, high strength and high elongation are easily obtained, and the properties after low-temperature heat treatment are also excellent. Coarse intermetallic compounds with an average equivalent circle diameter greater than 1.0 μm are not easy to obtain sufficient strength and elongation. For the same reason, the number density of intermetallic compounds with an equivalent circle diameter greater than 3.0 μm is 2.0×10 2 Pieces / mm 2 Below, preferably 1.0×10 2 Pieces / mm 2 the following.
[0039] Intermetallic compounds herein refer to particles that exhibit a contrast different from that of the aluminum matrix when observing the surface of an aluminum alloy foil using a scanning electron microscope and capturing a backscattered electron image (composition image). Intermetallic compounds include, but are not limited to, Al-Fe and Al-Fe-Si intermetallic compounds. However, particles composed solely of Si are not included in this analysis because they have a similar atomic number to aluminum and, in the aforementioned observation method, have no contrast difference from the aluminum matrix.
[0040] [Manufacturing method]
[0041] Next, a method for producing the aluminum alloy foil for a battery current collector according to the present invention will be described.
[0042] The method for producing aluminum alloy foil according to the present invention comprises: a casting step of preparing an aluminum mother alloy in a manner to be within the above-mentioned composition range, heating the aluminum mother alloy to produce an aluminum alloy melt, casting the aluminum alloy melt at a predetermined cooling rate to produce a cast plate; and a rolling step of cold-rolling the cast plate to produce a foil.
[0043] [Casting process]
[0044] An aluminum billet, various added metal elements or an aluminum master alloy containing them are prepared in a manner such that the iron (Fe) content is 0.15% by mass or more and less than 0.3% by mass, the silicon (Si) content is greater than 0.8% by mass and less than 1.5% by mass, and the remainder is composed of aluminum (Al) and inevitable impurities, and heated at 680-1000°C to form an aluminum alloy melt having the above composition. The melt is cast by TRC casting to produce a cast plate. In TRC casting, casting can be performed at a melt cooling rate of up to 250°C / sec or more. The casting thickness is not particularly limited. From the viewpoint of cooling rate and yield rate, a thickness of 5 to 8 mm is preferred.
[0045] In the present invention, TRC casting, which has a fast cooling rate for the melt during solidification, is preferred over general DC casting (Direct Chill Casting). Compared to the cooling rate of several to several tens of degrees Celsius / sec in DC casting, the cooling rate in TRC casting reaches 250 degrees Celsius / sec or more. By adopting TRC casting, the intermetallic compounds contained in the aluminum alloy foil are miniaturized, thereby achieving a highly supersaturated solid solution state of Fe and Si. Therefore, it is possible to obtain an aluminum alloy foil with high strength and high elongation while suppressing the Fe content to a low level. In addition, it is expected that the fine dispersion of the intermetallic compounds and the highly supersaturated solid solution state of Si are effective in suppressing the decrease in elongation after low-temperature heat treatment.
[0046] On the other hand, the upper limit of the cooling rate in TRC casting is not particularly limited, but may be 1000° C. / sec or less, preferably 600° C. / sec or less, from the viewpoint of the capacity of the TRC casting machine.
[0047] [Rolling process]
[0048] [Cold Rolling]
[0049] The obtained cast sheet is cold rolled by a conventional method to form aluminum alloy foil of a desired thickness. In order to improve the rollability and control the solid solution and precipitation state, one or more intermediate annealings may be performed during the cold rolling process.
[0050] [Intermediate annealing]
[0051] In the method for producing an aluminum alloy foil for a battery current collector according to the present invention, the intermediate annealing step is optional, but can be performed within a range that does not affect the characteristics of the aluminum alloy foil for the purpose of improving the rollability.
[0052] The intermediate annealing time is preferably 20 hours or less in terms of production efficiency. In addition, the intermediate annealing can be performed by batch annealing or by a continuous annealing line (CAL). When a continuous annealing line is used, rapid heating and rapid cooling are possible, thereby suppressing the precipitation of Fe or Si supersaturated in the aluminum alloy and improving the ductility, which is preferred.
[0053] [Homogenization heat treatment]
[0054] In the method for producing aluminum alloy foil for battery current collectors according to the present invention, it is preferred not to include a homogenization heat treatment step. If a homogenization heat treatment step is performed, the supersaturated solid solution of the added elements will precipitate during the casting step with a high cooling rate, resulting in coarsening of the structure. This may make it difficult to achieve the characteristics of the present invention, such as sufficient high strength and elongation.
[0055] [Hot Rolling]
[0056] In the method for producing aluminum alloy foil for battery current collectors according to the present invention, a hot rolling step is preferably not included. If a hot rolling step is performed, the supersaturated solid solution of the added elements will precipitate during the casting step with a high cooling rate, resulting in coarsening of the structure, which may make it difficult to achieve the characteristics of the present invention, such as sufficient high strength and elongation.
[0057] [Characteristics of Aluminum Alloy Foil]
[0058] [Resistivity]
[0059] The aluminum alloy foil for battery current collectors according to the present invention has a resistivity reduction of 0.03 μΩ·cm or more after heat treatment at 120°C for 1 hour relative to the resistivity after rolling, and more preferably 0.05 μΩ·cm or more. The resistivity reduction refers to the difference between the resistivity of the aluminum alloy foil after rolling and the resistivity of the aluminum alloy foil after heat treatment at 120°C for 1 hour. It is believed that even if the aluminum alloy foil is subjected to a low-temperature heat treatment at 120°C, strain recovery has almost no effect on the resistivity, and it is believed that precipitation of Al-Fe and Al-Fe-Si intermetallic compounds is unlikely to occur. Therefore, it is speculated that the resistivity reduction here is caused by the precipitation of elemental Si from the aluminum matrix. That is, in the present application, the resistivity reduction is proportional to the amount (concentration) of Si dissolved in the aluminum matrix that is precipitated by heat treatment. If the resistivity reduction is within the above range, the decrease in elongation after heat treatment at 120°C can be suppressed.
[0060] The term "after rolling" as used herein refers to a period from the time when the aluminum alloy foil is subjected to a foil rolling step and the aluminum alloy foil is cooled to room temperature to the time before the aluminum alloy foil is subjected to a low-temperature heat treatment at 120°C.
[0061] [Tensile strength, elongation]
[0062] The aluminum alloy foil for battery current collectors according to the present invention preferably has a tensile strength of 235 N / mm after rolling to a thickness of 12 μm. 2 More than, the elongation is preferably 3.0% or more, more preferably the tensile strength is 245N / mm 2 When the elongation is within the above range, the aluminum alloy foil can be prevented from breaking during the battery production process.
[0063] [Tensile strength and elongation after heat treatment at 120°C]
[0064] The aluminum alloy foil for battery current collectors of the present invention preferably has a tensile strength of 225 N / mm after heat treatment at 120°C for 1 hour with a thickness of 12 μm. 2 More than 2.5% elongation, more preferably a tensile strength of 240N / mm 2When the thickness falls within the above range, the aluminum alloy foil can be prevented from breaking during the battery production process.
[0065] [foil thickness]
[0066] The thickness of the aluminum alloy foil for battery current collectors according to the present invention is preferably 7 to 15 μm, more preferably 9 to 12 μm. If the thickness is less than 7 μm, flatness control and pinhole formation during rolling become problematic, and the foil is susceptible to breakage during battery manufacturing. If the thickness is greater than 15 μm, it cannot meet the demand for thinner foils.
[0067] Example
[0068] The following examples and comparative examples will further clarify the content of the present invention. First, the test methods used in the examples are described below.
[0069] (Test method)
[0070] [composition]
[0071] The compositions of the Examples and Comparative Examples were measured by inductively coupled plasma emission spectrometry. Examples of the measuring apparatus include iCAP6500DUO manufactured by Thermo Fisher Scientific, Inc., and ICPS-8100 manufactured by Shimadzu Corporation.
[0072] [Tensile test]
[0073] Short strip test pieces measuring 15 mm wide and 200 mm long were cut with the tensile direction parallel to the rolling direction. Tensile testing was performed using a Strograph VES5D manufactured by Toyo Seiki Seisaku-sho, Ltd., at a tensile speed of 3 mm / min and a gauge length of 100 mm between the chucks. Three tests were performed, and the average value was calculated. Tensile testing was performed after rolling and after heat treatment at 120°C.
[0074] [Intermetallic compounds]
[0075] The surface of the aluminum alloy foil was observed at a magnification of 1000 times using a field emission scanning electron microscope (JSM-7200F manufactured by JEOL Ltd.). In order to easily observe the intermetallic compounds, backscattered electron images (component images) were used for photography. The size of the intermetallic compounds was evaluated using the image analysis and measurement software WinROOF2021 (Mitani Shoji Co., Ltd. version 5.4.0). The contrast and brightness were adjusted by image processing within the analysis software to make the intermetallic compounds clear. Then, binarization was performed in a manner that could extract data of the intermetallic compound portion on the surface of the aluminum alloy foil by binarization based on a single threshold. Data processing was performed in the binarized data in a manner that deleted the portion with an equivalent circle diameter of less than 0.3 μm, and the average particle size of the intermetallic compound was calculated in the portion with an equivalent circle diameter greater than 0.3 μm. The reason for deleting the portion below 0.3 μm is that there is a high possibility that the data that is too small in the binarized data contains factors other than intermetallic compounds, such as tiny surface bumps. The number of intermetallic compounds with an equivalent circle diameter greater than 3.0 μm was also measured and the number per unit area was calculated. Images were taken randomly in five viewing fields and the average value was calculated.
[0076] [Resistivity]
[0077] Short test pieces measuring 15 mm wide and 200 mm long were cut with the rolling direction as the long side. The resistance of the test pieces was measured using a 3541 resistance meter manufactured by Hioki Electric Co., Ltd. after rolling and after heat treatment at 120°C. The distance between the terminals during measurement was 115 mm.
[0078] Resistivity ρ can be calculated as ρ = R·A / L. R is the resistance value, A is the cross-sectional area, and L is the length. Cross-sectional area A is the foil thickness x 15mm test piece width, and length L is the distance between the terminals (115mm).
[0079] (Examples 1 to 6, Comparative Examples 1 to 5)
[0080] Aluminum alloys with the compositions shown in Table 1 were melted, degassed, and subjected to inclusion removal treatment. The melt was then TRC cast to produce 7 mm thick cast plates. The cast plates were then cold rolled to produce aluminum alloy foils with thicknesses of 12 μm or 10 μm. The aluminum alloy foils were then heat treated at 120°C for 1 hour. The resulting aluminum alloy foils were subjected to the aforementioned tests. The results are shown in Table 1.
[0081] (Comparative Example 6)
[0082] Ingots were produced by DC casting according to the composition listed in Table 1. After surface milling, the ingots were subjected to homogenization heat treatment at the temperature listed in Table 1 and then hot rolled into 7 mm thick sheets. Cold rolling and a 120°C heat treatment were then performed in the same manner as in the Examples. The resulting aluminum alloy foils were subjected to the aforementioned tests. The results are shown in Table 1.
[0083]
[0084] [result]
[0085] In Examples 1 to 6, since the Fe and Si contents were within the prescribed range and the intermetallic compounds were fine due to TRC casting, excellent strength and elongation were obtained after rolling and 120° C. heat treatment.
[0086] On the other hand, in Comparative Examples 1 and 2, the Si content was lower than the prescribed value, and sufficient elongation after heat treatment at 120° C. could not be obtained.
[0087] In Comparative Example 3, the Si content exceeded the prescribed value, and the elongation after rolling was less than 3%. The aluminum alloy foil also had streaks on its surface, adversely affecting the elongation.
[0088] Furthermore, in Comparative Example 4, the Fe content was lower than the prescribed value, and the strength was insufficient both before and after the heat treatment.
[0089] In Comparative Example 5, the Fe content exceeded the prescribed value, and a sufficient elongation after heat treatment at 120° C. could not be obtained.
[0090] In Comparative Example 6, since the casting method was not TRC, the intermetallic compounds were coarse, and excellent values of strength and elongation could not be obtained.
Claims
1. An aluminum alloy foil for battery collector, characterized in that: (1) The aluminum alloy foil has a composition of 0.15 mass % or more and less than 0.3 mass % of iron (Fe), 0.8 mass % or more and less than 1.5 mass % of silicon (Si), and the remainder of aluminum (Al) and inevitable impurities. (2) the average equivalent circle diameter of the intermetallic compounds present on the surface of the aluminum alloy foil is 1.0 μm or less, (3) The number density of the intermetallic compounds with an equivalent circle diameter greater than 3.0 μm existing on the surface of the aluminum alloy foil is 2.0×10 2 Pieces / mm 2 the following.
2. The aluminum alloy foil for battery current collector according to claim 1, wherein The aluminum alloy foil has a resistivity after heat treatment at 120° C. for 1 hour with respect to the resistivity after rolling reduced by 0.03 μΩ·cm or more.
3. The aluminum alloy foil for battery current collector according to claim 1 or 2, wherein: The tensile strength after rolling with a thickness of 12 μm is 235 N / mm 2 Above, the elongation is 3.0% or more.
4. The aluminum alloy foil for battery current collector according to any one of claims 1 to 3, wherein The tensile strength after heat treatment at 120°C for 1 hour with a thickness of 12 μm is 225 N / mm 2 Above, the elongation is 2.5% or more.
5. A method for producing an aluminum alloy foil for a battery collector, comprising: A casting step of casting a molten metal having a composition of 0.15 mass % or more and less than 0.3 mass % of iron (Fe), 0.8 mass % or more and less than 1.5 mass % of silicon (Si), and the remainder consisting of aluminum (Al) and inevitable impurities at a cooling rate of 250° C. / sec or more to obtain a cast plate; and In the rolling step, the cast plate is cold-rolled to obtain an aluminum alloy foil.
Citation Information
Patent Citations
Aluminum alloy foil for battery power collection body and manufacturing method therefor
JP2017186629A
Aluminum alloy foil for current collector and method for producing the same
WO2010100924A1